2017
DOI: 10.1002/jmv.24810
|View full text |Cite
|
Sign up to set email alerts
|

Myalgic encephalomyelitis/chronic fatigue syndrome and gulf war illness patients exhibit increased humoral responses to the herpesviruses‐encoded dUTPase: Implications in disease pathophysiology

Abstract: Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) and Gulf War Illness (GWI) are debilitating diseases with overlapping symptomology and there are currently no validated tests for definitive diagnosis of either syndrome. While there is evidence supporting the premise that some herpesviruses may act as possible triggers of ME/CFS, the involvement of herpesviruses in the pathophysiology of GWI has not been studied in spite of a higher prevalence of ME/CFS in these patients. We have previously demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 47 publications
2
63
0
3
Order By: Relevance
“…A March 2017 report in Journal of Medical Virology describes common immune hyper-responsiveness and serum antibody profiles to viral proteins in Gulf War era veterans diagnosed with Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS). 16 Also in March 2017, psychiatric disorders among both U.S. veterans and those serving in allied forces during the Gulf War were also reported to be elevated, 17,15 and evidence of neurologic damage was identified in a study of U.S. Gulf War veterans conducted by investigators at Duke University and Harvard. 18 …”
Section: Introductionmentioning
confidence: 99%
“…A March 2017 report in Journal of Medical Virology describes common immune hyper-responsiveness and serum antibody profiles to viral proteins in Gulf War era veterans diagnosed with Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS). 16 Also in March 2017, psychiatric disorders among both U.S. veterans and those serving in allied forces during the Gulf War were also reported to be elevated, 17,15 and evidence of neurologic damage was identified in a study of U.S. Gulf War veterans conducted by investigators at Duke University and Harvard. 18 …”
Section: Introductionmentioning
confidence: 99%
“…We have previously found that a subgroup of patients diagnosed with ME/CFS exhibited a statistically significant elevation in antibodies against the EBV dUTPase protein. 19 In the present study we provide further evidence to support a mechanism by which abortive-lytic reactivation of a systemic latent infection of EBV and subsequent production of dUTPase protein, which occurs in a subgroup of patients with ME/CFS, could contribute to the development of a neuroinflammatory microenvironment in the brain by modulating BBB, microglia cell, and astrocyte gene expression/function, tryptophan, DA and serotonin metabolism, and synaptic plasticity, which in turn may contribute to the increased pain, postexertional fatigue, and cognitive impairments observed in some patients with ME/CFS.…”
Section: Discussionmentioning
confidence: 99%
“…More important, we have found that EBV dUTPase induces anxiety and sickness behaviors in mice 31,32 and that patients with ME/CFS have increased serum levels of antibodies to the EBV dUTPase. 19 The present study explored the contribution of EBV dUTPase protein, if any, in the neuroimmune dysfunction associated with ME/CFS with the use of in vitro and in vivo model systems.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we extended these studies to include ME/CFS patients from a “good day bad day study” and of the 74 patients examined (four longitudinal samples from each patient) 32.34% ( n = 24) were negative for antibodies to HHV-6, EBV-, and the human nuclear encoded dUTPase proteins. Some patients expressed antibodies to only HHV-6 (2.7%), EBV (5.41%), or human (6.76%) dUTPases, some co-expressed antibodies (20.27%) to the HHV-6 and EBV dUTPases, but the majority (28.38%) co-expressed antibodies to the HHV-6, EBV-, and human dUTPases [94]. These results not only suggest that there is reactivation of multiple herpesviruses in a subset of patients with ME/CFS, but also that the dUTPases are produced physiologically at sufficient levels to elicit a humoral response.…”
Section: Herpesviruses Dutpases and Human Diseasementioning
confidence: 99%